POTENTIAL YIELD OF ACID-ADAPTIVE SOYBEAN PROMISING LINES IN ULTISOLS OF TANAH LAUT REGENCY, SOUTH KALIMANTAN PROVINCE, INDONESIA - Heru Kuswantoro (SEAMEO BIOTROP, 2016)
Soybean is an important food commodity after rice and corn in Indonesia. Until now soybean demand cannot be fulfilled by domestic production, although the chances of fulfillment can be attempted. One of the attempts to increase domestic production is soybean planting in acid dry land that is widely available in Indonesia. The research aimed to obtain soybean lines that are adaptive in acid dry land. A total of 10 soybean promising lines and two check varieties (Wilis and Tanggamus) were grown in acid dry land in Tanah Laut Regency, South Kalimantan Province, Indonesia. Experimental design used was randomized complete block design with four replications. The data were analyzed using analysis of variance and followed by Least Significant Different test. The results showed that the promising lines of SC5P2P3.5.4.1-5 and SC5P2P3.23.4.1-5 achieved production of 1.51 t/ha and 1.48 t/ha, respectively. These yields were higher than Wilis and Tanggamus varieties that reached 1.41 t/ha and 1.13 t/ha, respectively. These two promising lines had the potency to be developed in Tanah Laut Regency, South Kalimantan or other areaswith similar soil characteristics.